Mewujudkan Generasi Muda yang Cinta Matematika: Pelatihan Aritmatika Sempoa untuk Siswa SDN Gunggung - Azizah, Lutfiana Fazat; Herowati, Herowati; Prijambodo, Raden Firman Nurbudi (-, 2025)
The abacus arithmetic training aims to enhance the mathematics skills of students at SDN Gunggung through an interactive approach. This activity successfully created a fun learning environment and motivated students to develop a greater interest in mathematics. By using the abacus as a learning tool, students more easily understood basic mathematical operations such as addition, subtraction, multiplication, and division. In addition to improving mathematical skills, this training also boosted students' confidence and improved their perception of mathematics. Teachers were actively involved by receiving special training so they could independently continue using this method. Support from parents further strengthened the success of the program, with reports indicating that children were more enthusiastic about learning mathematics at home. Challenges such as differences in students' abilities and the limited training time were addressed through a flexible approach and additional tutoring sessions. The impact of this activity was felt not only within the school but also opened up opportunities for further development. Future plans include expanding the training scope to higher grade levels, introducing more complex materials, and organizing abacus arithmetic competitions. This program shows great potential to sustainably improve the quality of mathematics education through close collaboration among teachers, students, and parents.